Естетика фольклоризму у творчості композитора Богдана Котюка - Гулянич, Ю. (Народна творчість та етнографія, 2007)
Creative work of the Ukrainian composer Bohdan Kotyuk is based on a wide range of stylistic preferences: from expression characteristic of the late/romanticism school to jazz principles of expression transformed into chamber and instrumental score. A peculiar place within this wide range of aesthetic views belongs to folk music and folklore creative method. One of the most vivid stylistic peculiarities of Bohdan Kotyuk’s creative work is his reference to different layers of Ukrainian folklore. Investigation into each aspect requires first of all distinct differentiation of approaches within the framework of the indivisible creative method.